Distinct phenotypes of stimulation-induced dysarthria represent different cortical networks in STN-DBS. (April 2023) - Lange, Florian; Eldebakey, Hazem; Hilgenberg, Alexandra; Weigl, Benedikt; Eckert, Marie; DeSunda, Angela; Neugebauer, Hermann; Peach, Robert; Roothans, Jonas; Volkmann, Jens; Reich, Martin M.
Abstract: Background: Deep brain stimulation of the subthalamic nucleus is an effective treatment of Parkinson's disease, yet it is often associated with a general deterioration of speech intelligibility. Clustering the phenotypes of dysarthria has been proposed as a strategy to tackle these stimulation-induced speech problems. Methods: In this study, we examine a cohort of 24 patients to test the real-life application of the proposed clustering and attempt to attribute the clusters to specific brain networks with two different approaches of connectivity analysis. Results: Both our data-driven and hypothesis-driven approaches revealed strong connections of variants of stimulation-induced dysarthria to brain regions that are known actors of motor speech control. We showed a strong connection between the spastic dysarthria type and the precentral gyrus and supplementary motor area, prompting a possible disruption of corticobulbar fibers. The connection between the strained voice dysarthria and more frontal areas hints toward a deeper disruption of the motor programming of speech production. Conclusions: These results provide insights into the mechanism of stimulation-induced dysarthria in deep brain stimulation of the subthalamic nucleus and may guide reprogramming attempts for individual Parkinson's patients based on pathophysiological understanding of the affected networks. Highlights: Phenotyping dysarthria variants in STN-DBS helps detect stimulation-induced side effects. These phenotypes can be explained by disturbances in different networks. This should guide DBS reprogramming attempts when speech disorders are present.